2017
DOI: 10.26460/jm.v7i2.279
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Gaya Kepemimpinan Dan Iklim Organisasi Terhadap Kepuasan Kerja Karyawan Di Rumah Sakit Umum Daerah Prambanan Sleman Daerah Istimewa Yogyakarta

Abstract: This study was conducted to determine the effect of leadership style and organizational climate on job satisfaction at Prambanan Public Hospital. This study was conducted on employees of RSUD Prambanan by the number of respondents as many as 100 employees. The number of respondents is determined by using purposive sampling technique. The data were collected by distributing questionnaires using a 5-point Likert scale to measure 18 indicators. Data analysis technique used was multiple linear regression. The test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Based on the results of Multiple Linear Regression Test 1, the calculation results are obtained for the leadership style variable with sig. of 0.006 indicates that the value is smaller than the probability of 0.05 (meaning 0.006 0.05) and the value of tcount is 2.885 ttable2.074.. n. This supports the research results [22] and Rohman [23]. Thus, if the leadership style is positive in directing employees and leading the institution, the organizational climate makes subordinates in carrying out their duties in the same direction and supports the leadership so that the organizational climate increases, employee performance will also increase and vice versa.…”
Section: Discussion Of Findingssupporting
confidence: 85%
See 1 more Smart Citation
“…Based on the results of Multiple Linear Regression Test 1, the calculation results are obtained for the leadership style variable with sig. of 0.006 indicates that the value is smaller than the probability of 0.05 (meaning 0.006 0.05) and the value of tcount is 2.885 ttable2.074.. n. This supports the research results [22] and Rohman [23]. Thus, if the leadership style is positive in directing employees and leading the institution, the organizational climate makes subordinates in carrying out their duties in the same direction and supports the leadership so that the organizational climate increases, employee performance will also increase and vice versa.…”
Section: Discussion Of Findingssupporting
confidence: 85%
“…The work climate variable (X2) has a positive influence on the lecturer performance variable (Y) [22]. In addition, research from [23] who concluded that leadership style had a positive and significant effect on employee job satisfaction…”
Section: The Influence Of Leadership Style On Employee Performancementioning
confidence: 99%
“…In terms of job satisfaction, several researchers have concluded, including Aruan & Fakri (2015), that partially the work environment has a positive and significant influence on employee job satisfaction. Rohman (2017) and Pio & Tampi (2018) Leadership style has a significant positive effect on employee job satisfaction. Wijaya (2018) and Safitri & Astutik (2019).…”
Section: Job Satisfactionmentioning
confidence: 99%